Vampires and zombies: transcultural migrations and transnational interpretations - Fischer-Hornung, Dorothea; Müller, Monika (University Press of Mississippi, 2016)
Essays that hunt down what happens when the undead go global
Description based upon print version of record
Keywords: Electronic books; Computerspiel; Massenmedien; Literatur; Zombie; Vampir